ANTHROPOPRAGMATIC STUDY OF PHRASEOLOGICAL UNITS IN UZBEK AND ENGLISH LANGUAGES - Turaeva, Shoira (Журнал иностранных языков и лингвистики, 2023)
This article investigates some aspects of phraseological units in English and Uzbek, as well as antropopragmatic aspects.